Obstacles and facilitators of cancer-related dyadic efficacy experienced by couples coping with non-metastatic cancers - Brosseau, Danielle C.; Peláez, Sandra; Ananng, Bethsheba; Körner, Annett (Frontiers in Psychology, 2023)
Cancer-related dyadic efficacy is an individual’s confidence to work together with a partner to conjointly manage the effects of cancer and its treatment. In other health contexts, higher levels of dyadic efficacy have been associated with fewer symptoms of psychological distress and higher ratings of relationship satisfaction. The aim of the current study was to explore patient and partner perspectives on what obstructs and facilitates cancer-related dyadic efficacy. These aims were accomplished through a secondary analysis of data collected as a part of a collective qualitative case study. Participants (N = 17 participants) were patients undergoing treatment or recently completed treatment (within 6 months) for a non-metastatic cancer and their partners. To enable in-depth discussions among participants, data was collected through five focus groups. Participants described obstacles and facilitators of dyadic efficacy as dimensions of a common influence. Consistent with these descriptions, reflexive thematic analysis was used to identify influences on cancer-related dyadic efficacy and their subsequent obstructive and facilitative dimensions. Four main categories of influence with the potential to obstruct or facilitate cancer-related dyadic efficacy were identified along with their subthemes: appraisals of the couple relationship (quality and togetherness), communication (pattern and interest in information), coping (strategy and evaluation), and responses to change (in tasks and roles and sex life). Eight obstructive and seven facilitative dimensions of these subthemes were described. This first analysis of obstacles and facilitators of couples’ cancer-related dyadic efficacy capitalized on the experiential expertise of individuals with cancer and their partners. These thematic results are instructive for the design of dyadic efficacy-enhancing interventions for couples coping with cancer.